The Role of School Leaders In Supporting Inclusive Educational Practices through Continuous Professional Developments: A Study among Selected Primary Schools in Abu Dhabi - ALARYANI, MANAL (2024)
Ensuring inclusive education practices for students with disabilities in mainstream schools poses significant challenges for school leaders. Despite legal frameworks emphasising inclusion, some leaders struggle to effectively integrate and accommodate these students due to a lack of clear approaches and professional development. This study investigated the role of school leaders in supporting inclusive educational practices through continuous professional development (CPD) in selected primary schools in Abu Dhabi. The rationale lies in the pivotal role school leaders play in implementing inclusive education, making it crucial to understand their perspectives and challenges. CPD training emerges as a key tool to equip leaders with strategies for promoting inclusive practices, aligning with evolving global trends. The study drew from leadership theories highlighting leaders’ influence in fostering inclusive cultures and Rabin’s foundational concepts emphasising meaningful learning, social interaction and student empowerment for effective inclusive practices. A sequential mixed-methods design involving document analysis, surveys (n=163 participants) and focus groups captured quantitative and qualitative data from leaders, teachers and parents. While indicating overall support for inclusion, the study revealed concerns about teacher qualifications, resource availability and implementation gaps across schools. Effective leadership practices, collaboration and cultural sensitivity emerged as critical factors. Policy implications underscore the need for refining inclusive education guidelines. Leadership training is crucial for creating inclusive environments. Professional development should empower educators with inclusive teaching strategies. Recommendations include specialised leadership programmes, ongoing teacher training, collaborative planning, equitable resource allocation and promoting cultural understanding through training to enhance inclusive practices. This comprehensive study offers insights into the multifaceted challenges of inclusive education and the pivotal role of school leaders. The recommendations serve as a roadmap for stakeholders to foster more inclusive learning environments through collaborative efforts, continuous improvement and a nuanced understanding of the complex educational landscape.